Massacre in Norway : the 2011 terror attacks on Oslo and the Utøya Youth Camp - Bromark, Stian, 1972- (Potomac Books, An imprint of the University of Nebraska Press, 2014)
On July 22, 2011, a bomb went off outside government buildings in Oslo, Norway, killing eight people and injuring more than two hundred. Less than two hours later, a gunman claimed sixty-nine lives in a shooting spree at a summer camp on the island of Ut?ya, while terrified and desperate youths tried to hide or swim to the mainland to escape. Massacre in Norway is the first detailed, hour-by-hour account of the two sequential terrorist attacks by lone-wolf terrorist Anders Behring Breivik. To inform his literary reportage, Stian Bromark compiled interviews with survivors, police officers, gove.